Selective Random CDD Enhanced Joint Cooperative Relay and HARQ for Delay-Tolerant Vehicular Communications. (19th May 2015) - Wu, Gang; Du, Qinghe; Hua, Kun
Abstract : We propose a selective random cyclic-delay diversity (CDD) enhanced joint cooperative relay and hybrid automatic repeat request (HARQ) scheme for two-hop vehicular communications. Our innovation mainly concentrates on design of the second-hop transmissions. On one hand, the CDD technique is applied across multiple relay nodes to artificially create frequency selectivity and then achieve diversity gain by applying channel coding. The employment of CDD does not necessarily require channel state information (CSI) at the transmitters and thus also decreases overhead caused by CSI feedback. On the other hand, retransmission for the second hop is performed based on relay selection. Particularly, the CDD is constructed only over selected relay nodes with qualified channel qualities to achieve a better frequency selective channel. As the selection results vary with random channel fading, our scheme is termed selective random CDD. Our scheme is presented based on a generic model and further applied into two scenarios, respectively: (1) car-to-car communications in high-way vehicular networks; (2) downlink transmission for the high velocity mobile station in cellular networks. Simulation results show that our proposed selective random CDD scheme can achieve higher throughput as well as lower transmission delay than the conventional cooperative beamforming based transmission scheme.